Perbandingan Kompetensi Pengetua Sekolah antara Malaysia dan Indonesia - Abdullah, Mustamin; Hj. Mohd. Yasin, M. Al Muzzammil (Sains Humanika, 2013)
The challenge of the education nowadays it is highly worrying for the school principals with low competencies as a educational leadership. The competence as a educational leadership in this research that meant is school leadership, instructional leadership and school operational leadership competence. It poses the result of document combination for school principalship competence specially Malaysia and Indonesia documents. There are 81 respondents from SMK Johor, Malaysia and 154 respondents from SMA Negeri Province of South Sulawesi Indonesia have participated in this research. The design of data analysis used is a analysis factor (Exploratory Factor Analysis-EFA and Confirmatory Factor Analysis-CFA), descriptive analysis and inferensial analysis. EFA and CFA results analysis shows that the competence dimensions used in this research generally to support significantly to the competence factor discussed. Meanwhile, the descriptive result shows that the competence of school principals level in Malaysia generally is more higher compared than the school principals competence in Indonesia. So on, Decision of hipotesis analysis shows to reject for null hipotesis that proposed.